Synthesis of Perovskite Nanocrystals and Their Photon-Emission Application in Conjunction With Liquid Crystals - Lin, Weixi; Nie, Qiumei; Jiang, Xiao-Fang; Jiang, Xinshuai; Wang, Kai; Shui, Lingling; Priya, Shashank; Zhou, Guofu; Hu, Xiaowen (Frontiers in Chemistry, 2020)
Perovskite nanocrystals have attracted worldwide attention due to their outstanding optical versatility, high photoluminescence quantum yields and facile synthesis. In this review, we firstly revisit the synthetic methods for perovskite nanocrystals (PNCs), including hot-injection, anion exchange, solvothermal reaction, etc. In the meantime, we discuss effects of different synthetic methods on the properties of PNCs, including the crystal size, emission spectral feature and quantum yield, etc., followed by several optimizing strategies. Finally, lasing and display applications of these PNCs in combination with liquid crystal materials are discussed thoroughly. Outlooks on challenges and opportunities of these nanocrystalline materials in terms of adjunct applications with liquid crystals have been presented at the end, which are highly promising for next-generation light-emission applications.